Influence of the production technology on kefir characteristics: Evaluation of microbiological aspects and profiling of phosphopeptides by LC-ESI-QTOF-MS/MS - Savastano, Maria Luisa; Pati, Sandra; Bevilacqua, Antonio; Corbo, Maria Rosaria; Rizzuti, Antonio; Pischetsrieder, Monika; Losito, Ilario (Food Research International, 2020)
The influence of production technology, namely, temperature, pH and 2-step fermentation (back-slopping approach), on the microbiological characteristics and on the phosphopeptide profile of kefir obtained with kefir grains was investigated. The growth of yeasts, lactic acid bacteria (LAB) and acetic acetic bacteria (AAB) in both grains and kefir was affected by the incubation temperature and by the use of back-slopping. In particular, at 25 °C the microbiota of kefir grains was mainly composed by LAB and yeasts, while at 18 °C yeasts represented the dominant group in kefir. Back-slopping at 25 °C determined a significant increase of AAB. A comprehensive characterization of potentially bioactive peptides, including caseino-phosphopeptides (CPPs), was performed, for the first time, in kefir obtained with kefir grains, using preliminary enrichment on hydroxyapatite followed by dephosphorylation and analysis by Liquid Chromatography-ElectroSpray Ionization-Quadrupole-Time of Flight-tandem mass spectrometry (LC-ESI-QTOF-MS/MS). As a result, seventy-three phosphopeptides, mostly arising from caseins (79% β-casein, 8% αs1-casein and 9% αs2-casein) and all including from three to five serine residues in their sequences, were identified. Seventy-one of them showed the typical motif “SerP-SerP-SerP-Glu-Glu”, which is crucial for the ability of caseins to bind to minerals. Several peptides were observed, for the first time, from the 1–40 region of β-casein. As for the effect of production technology, phosphopeptide profiles of kefirs obtained at 25 °C and 18 °C were very similar, whereas kefir produced under acidic conditions showed a predominance of smaller peptides, suggesting a higher level of proteolysis. Conversely, kefir obtained through back-slopping at 25 °C contained longer peptides, thus indicating a lower proteolytic activity and a poor reproducibility in the kefir phosphopeptide profile occurring when grains are reused.<br
Keywords: Kefir; LC-ESI-QTOF-MS/MS; caseino-phosphopeptides; kefir grains; fermentation; back-slopping